Quantitative Analysis of Ant Motion Using Video Tracking: Evidence of Quasi-Harmonic Oscillatory Behavior - Iskandar, Feri; Toifur, Moh (Lensa: Jurnal Kependidikan Fisika, 2026)
The motion of living organisms, including insects, often appears irregular and complex, making it difficult to describe using simple physical models. Nevertheless, certain biological movements may contain periodic components that can be approximated using basic motion models in physics. This study aims to analyze the movement of an ant using video tracking with the Tracker software to investigate whether its motion exhibits characteristics related to simple harmonic motion (SHM). Motion data were obtained from a recorded video with a frame rate of 20 fps and processed to determine the two-dimensional position projected onto a one-dimensional displacement axis, from which velocity and acceleration were derived using Tracker. The displacement–time analysis shows quasi-periodic fluctuations that can be approximated by a sinusoidal function with an amplitude of approximately 0.042 m and a frequency of about 0.21 Hz. The acceleration–displacement relationship shows a general negative trend consistent with the tendency predicted by SHM, although deviations from ideal linearity are observed. In addition, the velocity–displacement phase diagram does not form a clear elliptical pattern, indicating that the motion does not strictly follow ideal SHM behavior. These findings suggest that ant locomotion exhibits quasi-harmonic characteristics influenced by biological locomotion mechanisms and environmental interactions, demonstrating that video-based motion analysis provides a quantitative approach for examining oscillatory components in natural biological motion.